P025 Embedding paediatric PPIE in non-invasive ventilation interface design. (19th November 2019) - Barker, Nicki; Reed, Heath; McCarthy, Avril; Jeays-Ward, Kathy; Willox, Matt; Metherall, Pete; Elphick, Heather
Abstract : Introduction: Non-invasive ventilation (NIV) masks that fit well are difficult to find for children who are small or have atypical facial features. Poorly fitted masks create problems e.g. discomfort, non-adherence and facial deformity. Our project aims to design and produce masks that fit well. Children's voices are vital, but not often heard, in respiratory research projects. Integral to the research, we aimed to construct a patient and public involvement and engagement (PPIE) program designed to: Understand the problems children and families experience with NIV and establish their wants and needs Provide an inclusive and creative environment for non– constrained thinking Get actionable feedback and ideas for improvements from a diverse patient group Method: We created a method focussed on planning, innovation and participation (the PIP model). Session activities were designed to enable parents and children of all ages and abilities to participate. Examples include: Archery target activity – a method for realising the relative importance of patient's requirement (prioritisation). Graphic scribe recording – to reflect back to the children that they had been heard/understood and stimulate creative ideas. Use of technology – making short videos to help families understand concepts. Results: Our priorities and design brief changed as a result of the PPIE. The graphic scribe outputs formed part of the creative process whilst providing a unique and lasting resource. We are confident that we will produce NIV interfaces that are fit for real life purpose that people will want to trial. Discussion: For respiratory research to be truly successful, PPIE should be woven throughout a project, from concept to completion. It needs to be genuine and aligned with research aims. Time and effort spent enabling participation and creatively planning for inclusivity is rewarded by generating richer and more valuable information.